A persistence-weighted measure of core inflation in the euro area - Laurent Bilke; Livio Stracca (European Central Bank (ECB), 2008)
We propose a new core inflation measure for the Euro area which places the emphasis on the more lasting, i.e. persistent, price developments at a disaggregated level. The importance of each component of the HICP is reweighted according to its relative persistence, as measured by the sum of the autoregressive coefficients or by an indicator of mean reversion. Unlike headline inflation, our baseline core inflation measure is highly correlated with ECB monetary policy decisions, which could mean that it contains ex ante (pre monetary policy) information on inflationary pressure.
Keywords: E31; 330; core inflation; inflation persistence; Inflation; Verbraucherpreisindex; EU-Staaten